2015
DOI: 10.1177/0960327115600364
|View full text |Cite
|
Sign up to set email alerts
|

Identification of gene expression signature for cigarette smoke exposure response—from man to mouse

Abstract: Gene expression profiling data can be used in toxicology to assess both the level and impact of toxicant exposure, aligned with a vision of 21st century toxicology. Here, we present a whole blood-derived gene signature that can distinguish current smokers from either nonsmokers or former smokers with high specificity and sensitivity. Such a signature that can be measured in a surrogate tissue (whole blood) may help in monitoring smoking exposure as well as discontinuation of exposure when the primaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 66 publications
3
55
0
Order By: Relevance
“…These genes overlapped remarkably with genes present in previously published blood-based smoking gene signatures derived from the same datasets, constituting an independent confirmation of a signature proposed by Martin et al [27] and signatures from a meta-analysis of six studies that included a total of 10,233 subjects [50]. Many genes of the consensus signature are reported to undergo differential regulation at the mRNA and/or DNA methylation level following exposure to cigarette smoke (references in Supplementary table 7).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…These genes overlapped remarkably with genes present in previously published blood-based smoking gene signatures derived from the same datasets, constituting an independent confirmation of a signature proposed by Martin et al [27] and signatures from a meta-analysis of six studies that included a total of 10,233 subjects [50]. Many genes of the consensus signature are reported to undergo differential regulation at the mRNA and/or DNA methylation level following exposure to cigarette smoke (references in Supplementary table 7).…”
Section: Discussionsupporting
confidence: 85%
“…This finding confirmed that smoke has a prominent effect that propagates in blood cells distal to lungs, the primary site of exposure [20, 27]. Best-performing teams succeeded in (i) developing inductive models able to predict the class of new independent individual samples with high levels of performance (AUPR ≥0.93 for SC1 and SC2), and (ii) extracting parsimonious signatures that did not exceed 40 genes.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The 71 search results were further filtered to include datasets where the age, sex and smoking 72 status of the samples were reported ( Fig 1B). We found 3 datasets from GEO 73 (GSE42057 [21], GSE71220 [22], GSE54837 [23]) and 1 from AE (E-MTAB-5278 [24]) 74 that met our search criteria ( Table 1 and Fig 1B). We conducted an additional search 75 on GEO and AE to find healthy subjects with their smoking history reported to balance 76 our control subjects with our COPD subjects.…”
Section: Introductionmentioning
confidence: 99%